Evaluating Rural E-Government Web Service Using Design Thinking and COBIT 2019: A Case Study of Indramayu Regency - Widya Cholil; Tri Rahayu; Tjahjanto; Prihandoko; Vidyasagar Potdar (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study evaluates the maturity of public web services in Indramayu Regency, Indonesia, using a Design Thinking methodology combined with the COBIT 2019 Process Performance Model, aiming to clarify the digital governance gap in rural public service delivery. The research applies the five-stage Design Thinking process (Empathize, Define, Ideate, Prototype, Test) as an evaluation lens. Data were collected from 45 respondents through interviews, questionnaires, direct observations, and workshops with village officials. The COBIT 2019 Process Attribute Achievement Model was used to quantify capability maturity levels across each Design Thinking phase for 14 public web services in the regency. Most public web services scored only ‘Manage’ in the Empathize phase, with BPS Indramayu and PPID reaching ‘Established’. The Ideate, Prototype, and Test phases were predominantly ‘Performed’, with only BPS Indramayu and SIPADU reaching 'Managed'. These findings indicate that most platforms function primarily as informational websites with limited user-driven innovation, prototyping, and structured testing. This study offers a novel integrative framework that combines human-centered Design Thinking with COBIT 2019 governance assessment to assess the public sector web services of digital transformation in decentralized rural governance contexts, providing a scalable, empirically grounded model applicable to other rural communities.